Effects of Video-based Gesture Gaming on Hand Functions in Autistic Population: A Quasi-experimental Study - J Sangeetha Priya; Kalidasan Varathan (Journal of Clinical and Diagnostic Research)
Introduction: Autism is a complex neurodevelopmental disorder with broad spectrum of intricacies and challenges, affecting 1 in 100 individuals, as estimated by World Health Organisation (WHO). Symptoms mainly are related to behavioural abnormalities, motor control deficits and social communication issues. Video gaming technology are emerging as valid tool in the intervention protocols for autism, by showing significant improvements in motor strength and executive functions. Aim: To evaluate the impact of gesture gaming on dexterity, grip strength and working memory in individuals with autism. Materials and Methods: A quasi-experimental study was carried out at Krupanidhi College of Physiotherapy Outpatient Department (OPD) in Bengaluru, Karnataka, India. The duration of the study was one year, from June 2022 to June 2023. Subjects were selected primarily based on the Childhood Autism Rating Scale. Thirty autistic subjects were selected using convenient sampling and four different games were given for three alternate days for 12 weeks, lasting 40 minutes per session. Hand grip strength, visuo-spatial working memory and dexterity were measured by a dynamometer, Corsi-Block Tapping Test and the Jebsen-Taylor Hand Function (JTHF) test. Subjects from 11 to 16 years were considered. Statistical analysis was done using a paired t-test, with a significance level set at p-value<0.05. Results: After 12 weeks of intervention and 16 weeks of follow-up, significant difference (p-value<0.05) was noticed in all three variables. Hand grip strength for the right hand was measured at post-test (21.48±8.08) and follow-up (21.40±8.11), while for the left hand, it was post-test (13.26±3.75) and follow-up (13.15±3.76). Visuospatial Working Memory (VSWM) showed a backward span post-test (4.86±0.77) and follow-up (4.46±0.73) and forward span post-test (5.36±0.71) and follow-up (5.20±0.76). Dexterity for the non dominant hand was post-test (148.4±5.11) and follow-up (148.8±5.07), while for the dominant hand, it was post-test (138.8±7.86) and follow-up (139.0±7.86). Conclusion: Gaming technology has shown beneficial effects in improving hand grip strength, dexterity and working memory.